Розкол як форма боротьби ДПУ УСРР із православною церквою в Україні (1922–1927 рр.) - Тригуб, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
In article on the basis of wide sources’ base the place and a role of the GPU and its regional divisions in religious life, their organizational registration, specific features, structure and directions of work. The special attention addresses for a role of the given bodies in schism of Russian Orthodox Church in Ukraine in 1922–1927.